2012
DOI: 10.1007/s00392-012-0463-z
|View full text |Cite
|
Sign up to set email alerts
|

Green tea halts progression of cardiac transthyretin amyloidosis: an observational report

Abstract: Background Treatment options in patients with amyloidotic transthyretin (ATTR) cardiomyopathy are limited. Epigallocatechin-3-gallate (EGCG), the most abundant catechin in green tea (GT), inhibits fibril formation from several amyloidogenic proteins in vitro. Thus, it might also halt progression of TTR amyloidosis. This is a singlecenter observational report on the effects of GT consumption in patients with ATTR cardiomopathy. Methods 19 patients with ATTR cardiomyopathy were evaluated by standard blood tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 55 publications
1
74
0
3
Order By: Relevance
“…Left ventricular function is positively correlated with better prognosis in cardiac amyloidosis [158]. Though this study was very preliminary, without a control cohort, and the increase in left ventricular mass varied [159], the authors also found an increase in the mean mitral annular systolic velocity, a restorative effect, and a decrease in the total and low-density lipoprotein-associated cholesterol levels with no serious adverse events, suggesting that treatment with EGCG might be beneficial in these patients [157].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 63%
See 1 more Smart Citation
“…Left ventricular function is positively correlated with better prognosis in cardiac amyloidosis [158]. Though this study was very preliminary, without a control cohort, and the increase in left ventricular mass varied [159], the authors also found an increase in the mean mitral annular systolic velocity, a restorative effect, and a decrease in the total and low-density lipoprotein-associated cholesterol levels with no serious adverse events, suggesting that treatment with EGCG might be beneficial in these patients [157].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 63%
“…EGCG: A single-center observational study conducted in patients with familial amyloidotic TTR cardiomyopathy with an intake of 500-700 mg EGCG per day for 12 months, reported either no increase or a decrease in the left ventricular myocardial mass [157]. Left ventricular function is positively correlated with better prognosis in cardiac amyloidosis [158].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 99%
“…Following the observations that (-)-epigallocatechin-3-gallate (EGCG), the main polyphenolic constituent of green tea, reduces cerebral amyloidosis in Alzheimer transgenic mice (Rezai-Zadeh et al, 2005), and inhibits fibril formation of amyloid- (Ehrnhoefer et al, 2008), Dr Werner Hunstein, former professor of haematology at the University of Heidelberg, who was suffering from AL amyloidosis, observed an improvement in his cardiac symptoms while he was purposely drinking high amounts of green tea (Hunstein, 2007). The clinical activity of EGCG was then confirmed in retrospective case series both in AL amyloidosis and in transthyretin-related amyloidosis (ATTR) (Mereles et al, 2010;Kristen et al, 2012). A randomized clinical trial is ongoing to evaluate the ability of EGCG in promoting regression of residual cardiac damage in patients with AL amyloidosis who have completed chemotherapy.…”
Section: Review ª 2013 Blackwell Publishing Ltdmentioning
confidence: 97%
“…Epigallocatechin-3-gallate (EGCG), a green tea extract, seems to have an inhibitory effect on the formation of AL and ATTR amyloid. [82][83][84] A clinical trial has started to evaluate a possible role of EGCG in promoting regression of residual cardiac damage in patients with AL amyloidosis who have successfully completed chemotherapy. 67 An interesting development is the combined use of a drug called CPHPC and anti-SAP antibodies.…”
Section: Current Perspectivesmentioning
confidence: 99%